Cryptocurrencies as a Hedge and Safe Haven Instruments during Covid-19 Pandemic - Nensya Yuhanitha; Robiyanto Robiyanto (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2021)
This study examines the potential of cryptocurrencies such as Bitcoin, Ethereum, ripple, tether, and Bitcoin cash as hedging instruments and a safe haven for the Indonesian capital market, especially during the Covid-19 pandemic era. Now, Indonesia's capital market condition is in turbulence. The benefit of this research is to help the investors make decisions on which cryptocurrencies can be an instrument hedge and safe haven in this Covid-19 pandemic era for Indonesia Stock Exchange (IDX). The data used in this study are data on the closing price of the Composite Stock Price Index (CSPI), bitcoin (BTC), Ethereum (ETH), ripple (XRP), tether (USDT), and bitcoin cash (BCH) from January 3 to June 16, 2020. Data analysis used Generalized AutoregressiveConditional Heteroscedasticity (GARCH) and Quantile Regression (QREG). This study found that Bitcoin, Ethereum, tether, and Bitcoin cash can act as a hedge, but only the ripple cannot act as a hedge. Bitcoin, Ethereum, ripple, tether, and bitcoin cash cannot act as a safe haven when the Indonesian capital market was getting extreme, like during the Covid-19 pandemic era. The roles of Bitcoin, Ethereum, ripple, tether, and bitcoin cash as safe havens will fade when conditions in the Indonesian capital market become more extreme. This research can be used as a reference for investors for their investments by looking top four cryptocurrencies as a hedging instrument. However, in severe conditions such as during the Covid-19 Pandemic, the top five cryptocurrencies cannot be used as a safe haven, as revealed in this study.